PENGARUH KLOROFIL-A TERHADAP HASIL TANGKAPAN IKANLAYANG (Decapterus spp.) YANG DI DARATKAN DI PELABUHAN PERIKANAN NUSANTARA (PPN) SIBOLGA PROVINSI SUMATERA UTARA - Ewil Wiranda Sitorus; Ria Retno Sartika Manik; Mardame Pangihutan Sinaga (Journal of Research and Publication Innovation, 2025)
Layang fish is a type of fast swimmer, pelagic, sedentary and likes to group, lives in waters with high salt content (32-34 ppm) and likes clear waters. Layang fish are mostly caught in waters within 150-200 ml from the coast. Little is known about fish migration, but there is a tendency that during the day schools of fish move to deeper water layers and at night to the upper layers of water (TARIGAN, 2019). Chlorophyll-a is one of the indicator parameters of water fertility level found in phytoplankton. Chlorophyll-a concentration is commonly referred to as the photosynthetic pigment of phytoplankton photosynthesis. In marine waters, the chlorophyll-a index can be associated with fish production or more precisely, it can describe the level of productivity of fishing areas (Safruddin and Zainuddin, 2008).This research was conducted using the survey method, which is to collect existing data in the field by making direct observations by following the fishing process with fishermen for one month, and taking data on the catch of Kite fish at the Department of Marine and Fisheries, Silbolga Nusantara Fishing Port. Chlorophyll-a image data that will be overlaid with fish catches that have been categorized based on the number of catches and fishing units. The success of the fishing process carried out by fishermen depends on the fishing area, if you know the potential fishing area, it will facilitate fishermen in the fishing process. Fluctuations in catches are inseparable from several optimum oceanographic factors in these waters, namely, temperature and chlorophyll-a. Fish will look for the optimum temperature in their body and chlorophyll is useful for the food chain process in a body of water. The results of the regression test show that the concentration of chlorophyll-a has a “Moderately Strong Relationship” but there are also several factors that are not measured in this study that affect the catch of kite fish.